Pendekatan Sosial Budaya Dalam Perencanaan Wilayah Berbasis Sejarah Analisis Pengembangan Kawasan Wisata Benteng Otanaha di Gorontalo - Muhammad Rejki Zakaria; Yayuk Septiani Kunai; Sriantika Y Djani; Wahyudin W; Sunarty Suly Eraku; Moch. Rio Pambudi (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Otanaha Fort tourist attraction is located on a hill in Dembe 1 Village, West City District, Gorontalo City. The purpose of this research is to find out the strengths, weaknesses, opportunities, and threats of the otanaha fort tourist attraction to find the right strategy to develop the tour. the method used is SWOT analysis and descriptive geo tourism development matrix with primary and secondary data collection. The results showed the importance of utilizing strengths such as innovation and infrastructure, overcoming weaknesses in marketing and service quality, taking advantage of opportunities in tourism programs and natural beauty, and managing threats from economic instability and cultural preservation issues.Amalia, Khorina Dwi Disti, Hayati, Nunung Nuring, & Alfiah, Rindang. (2021). Persepsi Wisatawan Terhadap Daya Tarik Desa Kemiren Sebagai Desa Wisata Menggunakan Metode Importance PerformanceAnalysis(IPA)1TouristPerceptionsoftheAttractivenessofKemirenVillageasa Tourist Village Usingthe Importance Performance Analysi. MATRAPOLISJurnalPerencanaan Wilayah Dan Kota, Vol. 2(No. 2), 95–108.DwiRandayaniButulipu,IvanTaslim,AhmadSyamsuRijal.(2018).SpatialDevelopmentofOtanaha Castle In Gorontalo Cultural Heritage. Sains Informasi Geografi[Jsig], I(1), 8–16.Gössling,S.,&Scott,D.(2021).Thedecarbonizationofthetourismsystem:progress,challenges, and opportunities. Journal of Sustainable Tourism, 29(1), 102-122.Gössling,S.,&Hall,C.M.(2021).Sustainabletourism:Aglobalperspective.JournalofSustainable Tourism, 29(4), 482-497.Gössling,S.(2021).DecarbonizingtourismHall, C. M., & Page, S. J. (2020). The Routledge Handbook of Tourism Research. Routledge. Nidaa,Izzatun,&Krianto,Tri.(2022).ScopingReview:FaktorSosialBudayaTerkaitPemberianAsiEksklusifDiIndonesia.JurnalLitbangKotaPekalongan,20(1),9–16.Rahmad,WahyuAnnur,Koniyo,MohHidayat,&Zakaria,Alfian.(2024).Video360PengenalanObjek Wisata BentengOtanahaDiProvinsiGorontaloDenganMetodeMdlc. 4(1), 10–17.Setyowati,RatnaDewi,&Setiawan,Eli.(2021).PELAKSANAANTEDHAKSITENPADAMASYARAKAT JAWA DILIHAT DENGAN PENDEKATAN SOSIAL BUDAYA (Studi Kasus di Desa Keniten, Kec.Ponorogo,Kab.Ponorogo).OpiniaDeJournal,1(1),83–96.Retrievedfrom http://ejournal.stainumadiun.ac.id/index.php/opinia/article/view/6/6Sunarti, Sri, Ntobuo, Fendi, & Machmud, Joice. (2022). “Pemberdayaan Wisata Sejarah Benteng OtanahaUntukMeningkatkanPerekonomianPendudukDiKelurahanDembe1KotaGorontalo.” Prosiding Seminar Nasional UNIMUS, 5, 1715–1723. Retrieved from https://prosiding.unimus.ac.id/index.php/semnas/article/view/1127%0Ahttps://prosiding.unimus.ac.id/index.php/semnas/article/viewFile/1127/1125Sigala,M.(2022).Socialmediainthetourismindustry:Aconceptualframework. Tourism Management Perspectives, 43, 100952.Sharpley,R.(2021).Tourism,development,andtheenvironment:Challengesandopportunities.Current Issuesin Tourism,24(5),622-637.Scheyvens,R.(2020).Tourismandpoverty. TourismEconomics,26(3),417-434.Weaver,D.B.(2020).Theconceptofsustainabletourism:Anevolvingparadigm.AnnalsofTourism Research, 84, 102935.Wang,Y.,&Pfister,R.E.(2020).Community-basedtourismandsustainabledevelopment.Journalof Ecotourism, 19(4), 245-260.Weaver,D.B.(2020).Core-peripheryrelationshipsintourism.AnnalsofTourismResearch,84, 102931.